Cancer : oxidative stress and dietary antioxidants - Preedy, Victor R. (Academic Press, 2014)
Cancer: Oxidative Stress and Dietary Antioxidants bridges the trans-disciplinary divide and covers in a single volume the science of oxidative stress in cancer and then the potentially therapeutic usage of natural antioxidants in the diet or food matrix. The processes within the science of oxidative stress are described in concert with other processes such as apoptosis, cell signaling, and receptor mediated responses. This approach recognizes that diseases are often multifactorial and that oxidative stress is a single component of this. Oncologists, cancer researchers, and nutritionists are separated by divergent skills and professional disciplines that need to be bridged in order to advance preventative as well as treatment strategies. While oncologists and cancer researchers may study the underlying pathogenesis of cancer, they are less likely to be conversant in the science of nutrition and dietetics. On the other hand, nutritionists and dietitians are less conversant with the detailed clinical background and science of oncology. This book addresses this gap and brings each of these disciplines to bear on the processes inherent in the oxidative stress of cancer.